2021
DOI: 10.2337/dc20-3112
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of a Proactive, Three-Level Strategy to Identify People With Prediabetes in a Large Workforce With Employer-Sponsored Health Insurance

Abstract: OBJECTIVE Rates of diagnosis of prediabetes and uptake of the National Diabetes Prevention Program (NDPP) are low. We evaluated a proactive three-level strategy to identify individuals with prediabetes in a population with employer-sponsored health insurance. RESEARCH DESIGN AND METHODS We studied 64,131 insured employees, dependents, and retirees ≥18 years of age without diagnosed diabetes, 19,397 (30%) of whom were estimated to have prediabetes. Individuals with predi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 21 publications
0
10
0
Order By: Relevance
“…There is also evidence that joint parent-child interventions and parent-only interventions lead to direct effects on children's weight loss (10)(11)(12)(13)(14)(15). Given these past studies and the demonstrated efficacy of DPPs in promoting the adoption of healthy diet and activity habits (18), parental participation in the DPP might lead to improvements in BMI percentile of their dependent children. However, in this study, parental participation in the DPP was not specifically designed to influence children's BMI percentile.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is also evidence that joint parent-child interventions and parent-only interventions lead to direct effects on children's weight loss (10)(11)(12)(13)(14)(15). Given these past studies and the demonstrated efficacy of DPPs in promoting the adoption of healthy diet and activity habits (18), parental participation in the DPP might lead to improvements in BMI percentile of their dependent children. However, in this study, parental participation in the DPP was not specifically designed to influence children's BMI percentile.…”
Section: Discussionmentioning
confidence: 99%
“…Beginning in August 2015, a large research university in the Midwestern United States offered its self-insured employees, dependents, and retirees with prediabetes and obesity the option of participating in a one-year DPP at no out-of-pocket cost. The university used a tiered intervention strategy to identify individuals with prediabetes (18). Between 2015 and 2018, individuals with prediabetes were sent letters encouraging them to join a DPP (18).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We identified 64,131 university employees, dependents, and retirees ≥ 18 years of age without evidence of Type 1 or Type 2 diabetes mellitus and identified 8,131 of them (12.7%) as having prediabetes and overweight or obesity based on health plan records [ 5 ]. Prediabetes was defined by either a health plan claims diagnosis of prediabetes or a hemoglobin A1c (HbA1c) level of 5.7 to 6.4% (39 to 46 mmol/mol).…”
Section: Subjects Materials and Methodsmentioning
confidence: 99%
“…These strategies were described previously. 16 Strategy 1 (members with pre-diabetes) Enrollment, claims, pharmacy, and laboratory data were used to identify Premier Care members ≥18 years of age without evidence or diagnoses of diabetes mellitus but with one or more of the following: (1) claims for impaired fasting glucose (International Classification of Diseases, Ninth revison (ICD-9) 790.21 or ICD, Tenth revision (ICD-10) R73.01), impaired glucose tolerance (ICD-9 790.22 or ICD-10 R73.02), or other abnormal glucose (ICD-9 790.29 or ICD-10 R73, R73.0, R73.09, and R73.9), and (2) hemoglobin A1c (HbA1c) levels between 5.7% (39 mmol/mol) and 6.4% (46 mmol/mol) in the preceding 3 years (ADA criterion for pre-diabetes). 17 Every 6 months, these criteria were used to identify individuals with pre-diabetes.…”
Section: Methodsmentioning
confidence: 99%